Association of Varroa destructor females in multiply infested cells of the honeybee Apis mellifera. (2nd November 2017) - Beaurepaire, Alexis L.; Ellis, James D.; Krieger, Klemens J.; Moritz, Robin F. A.
Abstract: The genetic diversity of Varroa destructor (Anderson & Trueman) is limited outside its natural range due to population bottlenecks and its propensity to inbreed. In light of the arms race between V. destructor and its honeybee ( Apis mellifera L.) host, any mechanism enhancing population admixture of the mite may be favored. One way that admixture can occur is when two genetically dissimilar mites coinvade a brood cell, with the progeny of the foundresses admixing. We determined the relatedness of 393 pairs of V. destructor foundresses, each pair collected from a single bee brood cell ( n = five colonies). We used six microsatellites to identify the genotypes of mites coinvading a cell and calculated the frequency of pairs with different or the same genotypes. We found no deviation from random coinvasion, but the frequency of cells infested by mites with different genotypes was high. This rate of recombination, coupled with a high transmission rate of mites, homogenized the allelic pool of mites within the apiary.